Differences in the three-dimensional typing forces between short and long travel keyboards. (September 2014) - Hughes, Margaret; Johnson, Peter W.
Keyboards with shorter key travel are becoming widespread yet it is unknown whether there are any biomechanical differences in the typing forces when using these keyboards. If one keyboard promotes typing with more force, this may increase the risk for developing an upper extremity disorder. A total of 17 subjects typed on two short travel keyboards (<2.5 mm) and one long travel keyboard (4.0 mm). The magnitude and angle of the typing forces were measured in the x-, y- and z-axes using a thin, three-dimensional force platform. The aim of this study was to determine whether there were differences between the short and long travel keyboards in the magnitude and direction of the typing forces and the keystroke durations. In addition we wanted to determine whether there were typing force differences between key rows, hands, and fingers. Keyboards with shorter key travel resulted in less extreme angles and smaller magnitudes for forces applied in the x and y directions. Shorter travel distances were associated with smaller peak and mean vector sum forces and shorter keystroke durations. Although these results indicate keyboards with shorter key travel affect typing biomechanics, it is uncertain whether the small differences in keystroke durations and applied typing forces are physiologically meaningful and would reduce a computer user's risk for developing an upper extremity musculoskeletal disorder.